ANALYSIS OF THE CURRENT STATE OF THE USE OF GAMIFICATION ELEMENTS IN THE TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS - Aldabergenova, А.О.; Yesseikyzy, Ұ.; Kydurbayeva, Г.Т.; Yesseikyzy, А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article conducts an examination of the current utilization of gamification elements within the education of prospective computer science educators. The research paper entails an analysis of psychological and pedagogical literature pertaining to gamification, with particular emphasis on motivational factors influencing the learning process. Moreover, it scrutinizes the advantages and disadvantages of gamification, drawing from the works and research conducted by scholars, particularly in relation to its impact on students' academic progress. To ascertain the extent of gamification element integration in education, a survey was administered to instructors within the educational programs "Informatics" and "Mathematics-Informatics" at Zhetysu University, named after I. Zhansugurov. This survey also aimed to identify factors impeding the implementation of gamification elements in the educational process. Based on the research outcomes, the study advocates for the development of an advanced training program for computer science educators at the university, specifically tailored to incorporate gamification elements into their teaching methodologies.